2012
DOI: 10.1260/1756-8277.4.2.155
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Homogeneous Chemistry during Ignition of Propane Combustion in Pt-Catalyzed Microburners

Abstract: The aim of this work is to numerically investigate the ignition behavior of homogeneousheterogeneous (HH) combustion of propane in a Pt-catalyzed microburner to delineate the role of homogeneous chemistry during cold-start ignition. A two dimensional model with one-step homogeneous and catalytic mechanisms in a parallel-plate microburner is considered. The ignition characteristics (ignition temperature and ignition time) are explored for catalytic microreactor with and without homogeneous chemistry. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The kinetic rate parameters are given in Table 1, whereas the activation energy for oxygen desorption is taken from ref. 35 and evaluated as:…”
Section: Model Description and Solution Methodologymentioning
confidence: 99%
“…The kinetic rate parameters are given in Table 1, whereas the activation energy for oxygen desorption is taken from ref. 35 and evaluated as:…”
Section: Model Description and Solution Methodologymentioning
confidence: 99%
“…The catalytic combustors emerge as one of the promising technologies for the occurrence of the combustions in microchannels [3]. They do provide a higher surface area per reactor volume for the chemical reactions, thereby broadening the stability limits [4], facilitating the ignition at low temperatures [5], and suppressing the flame instabilities [6]. Indeed, catalytic combustors enable clean combustion of both low and high calorific values on the surface of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experiments along with simulations have been demonstrated that the homogeneous chemistry cannot be ignored, especially at high temperatures and pressures [9e12]. The contribution of homogeneous chemistry in these HH microreactors varies with conditions and application [13,14]. In general, homogeneous combustion can be desirable or detrimental, depending on the specific application and conditions of the system [15].…”
Section: Introductionmentioning
confidence: 99%